Effect of ginger extract on Mutans streptococci in comparison to chlorhexidine gluconate - Tuqa Akram Weli; Ahlam Taha Mohammed (College of Dentistry/ University of Baghdad, 2014)
Background: The rhizome of ginger is used in cooking and for medicinal purposes such as anti-bacterial, anti-fungal, anti-inflammatory and antioxidant. The aims of the study were to test the effect of ethanolic extract of ginger on growth, adherence and acidogenicity of mutans streptococci in comparison to chlorhexidine gluconate 0.2% and de-ionized water. Materials and methods: From saliva often volunteers (dental students 20-22 years); mutans streptococci was isolated, purified and diagnosed according to morphological characteristic and biochemical tests. Ginger was powdered and extracted, different concentrations of ginger extract were prepared. Chlorhexidine gluconate 0.2% used as a control positive; while de-ionized water was used as a control negative. In this study, in vitro and in vivo experiments were conducted. In vitro experiment, agar well technique was used to study the sensitivity of mutans streptococci to different concentrations of ginger extract and other control agents; also effect of ginger extract on the viable count of mutans streptococci, the adherence and acidogenicity of mutans streptococci were studied.In vivo experiment, the volunteers couldnt tolerate the extract. Results: Mutans streptococci was sensitive to different concentrations of ethanolic ginger extract, but they were more sensitive to chlorhexidine gluconate than the extract. The effect of ginger extract on the viable count of mutans streptococci at concentrations (30%, 35% and 40%) showed highly significant reduction in the count of the bacteria but less than chlorhexidine effect. In the effect of the extract on the adherence of mutans streptococci, the concentrations (30%, 35%, 40%) were used and only 40% and chlorhexidine prevent the plaque formation. But in the acidogenicity of mutans streptococci procedure 35%, 40% of the extract and chlorhexidine showed effectiveness in reducing acid formation. Conclusion: Ginger extract was effective against mutans streptococci, chlorhexidine is more effective than other agents.